Analysis of the location determination of public electric vehicle charging stations in supporting battery-powered electric vehicle policies in the eastern java region - Hakim, Arif Rochman (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
The current increase in greenhouse gas emissions is a serious concern of various parties both from the community and the government. and one of the biggest contributors is from the transportation side, especially conventional land transportation made from fossil fuels. To deal with this situation, one solution is to switch to using electric vehicles. The Indonesian government itself is fully committed to reducing greenhouse gas emissions, one of which is by issuing Perpres No. 55 of 2019 concerning the development of battery - based electric vehicles. However, this effort is still not enough to attract consumers. This is very reasonable because of the lack of supporting facilities for the electric vehicle it self. one of them is the electric vehicle battery charging station (SPKLU). So that the need to increase the number of electric vehicle charging stations in order to attract consumer interest, with the increasing number of SPKLU will certainly increase the sense of security and comfort for electric vehicle users. Therefore, the purpose of this study is to determine the ideal location of public electric vehicle charging stations (SPKLU), especially in the East Java region and the application is carried out in the city of Probolinggo. The analysis method used in this research is factor analysis to determine the factors that influence consumers in choosing an electric vehicle charging station, then mapping the optimal alternative travel path in the East Java region using the Dynamic Programming method with the Backward Reqursive Equation procedure, then weighting each criterion using the Analytical Hierarchy Process method, and then determining the priority of the ideal SPKLU location using the Composite Performance Index method. The results of the calculation of this study obtained the ideal SPKLU location with the application in the Probolinggo city area, namely at Sukabumi Gas Station as the first priority in placing the location of the public electric vehicle charging station.